Molecular markers of disease severity and response to nusinersen therapy in 5q spinal muscular atrophy (literature review) - K. D. Popov; T. M. Alekseeva; V. D. Nazarov; A. I. Vlasenko; S. M. Malyshev (Нервно-мышечные болезни)
Currently, there are three drugs in the world for the pathogenetic therapy of spinal muscular atrophy 5q: nusinersen, risdiplam and onasemnogene abeparvovek. At the same time, it is still unknown to what extent this treatment is able to change the natural history of the disease, and the development of methods for evaluating the effectiveness of treatment is the subject of active scientific research. This article is a review of studies of laboratory approaches for assessing the disease severity and the response to nusinersen therapy in patients with spinal muscular atrophy 5q in various age groups.